Adiwiyata-Based Learning dalam Penguatan Ecological Awareness dan Green Mindset Siswa - Midya Yuli Amreta; Nasywa Qorriayna La'aly; Humay Rosyaida; Putri Aualia Reviana; Erly Sintia Putri; Mirda Aini Fahma; Siti Mukholifah; M. Fahmi Wafiyudin; Chafidatur Rohmatika; Ulfa Nurfitri Aprilia; Neyha Fadlilatul A'inia (GUYUB: Journal of Community Engagement, 2026)
Low ecological awareness among students remains a challenge in fostering an environmentally responsible school culture. Initial observations at MI Islamiyah Tulungagung revealed that some students still disposed of waste improperly, paid limited attention to classroom cleanliness, and had not yet developed habits of conserving water. These conditions formed the basis for selecting the school as the community service site and highlighted the need to strengthen students’ ecological awareness and green mindset through Adiwiyata-based learning. This community service program employed the Participatory Action Research (PAR) approach, consisting of problem identification, planning, implementation, mentoring, reflection, and evaluation. The activities included environmental awareness campaigns, the integration of environmental values into classroom learning, the habituation of environmentally friendly behaviors, and assistance in school cleanliness and greening programs. The results showed that 85% of students demonstrated environmentally responsible behaviors, such as disposing of waste properly, maintaining classroom cleanliness, and conserving water, while 80% showed improved understanding of environmental preservation. In addition, 78% of students actively participated in school greening and plant maintenance activities. These findings indicate that Adiwiyata-based learning is effective in enhancing students’ ecological awareness and fostering a sustainable green mindset. Therefore, the program is recommended for continuous implementation through collaboration among schools, teachers, students, and parents to strengthen an environmentally conscious school culture.